2024
DOI: 10.1186/s40001-023-01574-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between blood lipids and cognitive impairment in type 2 diabetes mellitus

Li Ma,
Yue-Xing Yuan,
Feng-Jin Cheng
et al.

Abstract: Objective The study was performed to explore the association between blood lipids and cognitive impairment in patients with type 2 diabetes mellitus (T2DM). Methods This study included 336 patients with T2DM. Relevant clinical data including total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), apolipoprotein A1, apolipoprotein B were collected, and the Mini-Mental Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In contrast, in a study that evaluated 290 patients with DM-2, it was observed that elevated LDL cholesterol was a risk factor for mild CD (OR = 1.635, p = 0.047), concluding that mild CD is frequent among DM-2 patients [ 51 ]. On the other hand, the finding from another study showed no correlation between the levels of total cholesterol, LDL-cholesterol, HDL-cholesterol, and TG and apolipoprotein B and CD, except for apolipoprotein A1 levels, which were independently associated with CD (OR = 5.201, p = 0.024) and correlated negatively to significant MMSE scores (r = −0.132, p = 0.016) and MoCA scores (r = −0.143, p = 0.009) [ 52 ]. In our study, we also demonstrated that, in diabetic patients, the presence of hyperlipidemia increased the risk of a reduced MMSE score, and thus of developing CD or dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a study that evaluated 290 patients with DM-2, it was observed that elevated LDL cholesterol was a risk factor for mild CD (OR = 1.635, p = 0.047), concluding that mild CD is frequent among DM-2 patients [ 51 ]. On the other hand, the finding from another study showed no correlation between the levels of total cholesterol, LDL-cholesterol, HDL-cholesterol, and TG and apolipoprotein B and CD, except for apolipoprotein A1 levels, which were independently associated with CD (OR = 5.201, p = 0.024) and correlated negatively to significant MMSE scores (r = −0.132, p = 0.016) and MoCA scores (r = −0.143, p = 0.009) [ 52 ]. In our study, we also demonstrated that, in diabetic patients, the presence of hyperlipidemia increased the risk of a reduced MMSE score, and thus of developing CD or dementia.…”
Section: Discussionmentioning
confidence: 99%